Impact of Cervical Dystonia on Work Productivity: An Analysis From a Patient Registry. Issue 2 (16th December 2015) - Molho, Eric S.; Stacy, Mark; Gillard, Patrick; Charles, David; Adler, Charles H.; Jankovic, Joseph; Schwartz, Marc; Brin, Mitchell F.
Abstract: Background: Cervical dystonia is thought to result in high disease burden, but limited information exists on its impact on employment and work productivity. We utilized data from the Cervical Dystonia Patient Registry for the Observation of OnabotulinumtoxinA Efficacy (ClinicalTrials.gov identifier: NCT00836017) to assess the impact of cervical dystonia on employment and work productivity and examine the effect of onabotulinumtoxinA treatments on work productivity. Methods: Subjects completed a questionnaire on employment status and work productivity at baseline and final visit. Baseline data were examined by severity of cervical dystonia, predominant subtype, presence of pain, prior exposure to botulinum toxin, and/or utility of a sensory trick. Work productivity results at baseline and final visit were compared in subjects who were toxin‐naïve at baseline and received three onabotulinumtoxinA treatments. Results: Of 1, 038 subjects, 42.8% were employed full‐ or part‐time, 6.1% unemployed, 32.7% retired, and 11.8% disabled. Of those currently employed, cervical dystonia affected work status of 26.0%, caused 29.8% to miss work in the past month (mean, 5.1 ± 6.4 days), and 57.8% reported decreased productivity. Half of those unemployed were employed when symptoms began, and 38.5% attributed lost employment to cervical dystonia. Pain, increasing severity, and anterocollis/retrocollis had the largest effects on work status/productivity. Preliminary analyses showed that absenteeism and presenteeism were significantly decreased following onabotulinumtoxinA treatments in the subpopulation that was toxin‐naïve at baseline. Conclusions: This analysis confirms the substantial negative impact of cervical dystonia on employment, with cervical dystonia‐associated pain being a particularly important driver. OnabotulinumtoxinA treatment appears to improve work productivity.